2021
DOI: 10.1038/s41467-021-23344-0
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective activation of benzocyclobutenones and dienamides lead to anti-Bredt bridged-ring systems by a [4+4] cycloaddition

Abstract: To the best of our knowledge, bridgehead carbon benzofused-bridged ring systems have previously not been accessible to the synthetic community. Here, we describe a formal type-II [4 + 4] cycloaddition approach that provides fully sp2-carbon embedded anti-Bredt bicyclo[5.3.1] skeletons through the Rh-catalyzed C1–C8 activation of benzocyclobutenones (BCBs) and their coupling with pedant dienamides. Variously substituted dienamides have been coupled with BCBs to provide a range of complex bicyclo[5.3.1] scaffold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The deuterium was transferred intramolecularly from the olefinic position to the methyl group (eq 2, Scheme ). The 50% incorporation of deuterium was attributed to the scrambling of transiently formed Cl 2 (nbd)­Rh-D from DCl and (nbd)­RhCl with nbd . However, the deuterium transfer undoubtedly demonstrated that C olefin –H can be selectively activated and is in good agreement with the mechanism.…”
mentioning
confidence: 65%
“…The deuterium was transferred intramolecularly from the olefinic position to the methyl group (eq 2, Scheme ). The 50% incorporation of deuterium was attributed to the scrambling of transiently formed Cl 2 (nbd)­Rh-D from DCl and (nbd)­RhCl with nbd . However, the deuterium transfer undoubtedly demonstrated that C olefin –H can be selectively activated and is in good agreement with the mechanism.…”
mentioning
confidence: 65%
“…1b ) 43 47 . However, challenges remain in this area, including: (1) derivatization of BCBs to those that are heteroarene-fused remains elusive; (2) these transformations are mainly limited to the intramolecular versions due to the high reactivity of in situ formed metallacycle species; (3) the unsaturated units for [4 + 2]-cycloaddition have been primarily restricted to alkenes 48 51 , alkynes 52 55 , carbonyls 56 , oximes 57 , allenes/1,3-dienes 58 , and heteroarenes 59 , but imines and other readily available nucleophilic reagents are still unexploited; (4) only few catalytic asymmetric methods have been reported, and the asymmetric synthesis of chiral (hetero)arene fused heterocycles represents a significant challenge 60 65 . To address these limitations, the development of a platform molecule as a versatile C4 synthon is a pivotal aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transition-metal catalyzed C(sp 3 )–C bond activation and functionalization of ketones have received remarkable attraction, despite the substrate scope being limited to either 1,3-dicarbonyl 14 or strained motifs. 11 d ,15 Additionally, directing groups 16 and/or high temperatures 17 are often required for successful activation. Most recently, photochemistry has been utilized as an efficient method to address these issues, and cyclic ketone-derived oxime esters and oxime carboxylic acids have been successfully installed with α-trifluoromethyl alkenes to forge gem -difluoroalkenes.…”
Section: Introductionmentioning
confidence: 99%